2019
DOI: 10.1016/j.trf.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Don’t shoot the messenger: Traffic-irrelevant messages on variable message signs (VMSs) might not interfere with traffic management

Abstract: Road authorities struggle with the question whether variable message signs (VMSs) should exclusively be used for traffic management or could also be used to display traffic-irrelevant messages, such as mottos or commercial advertisements. The current study assesses behavioural responses to a critical route instruction displayed on the same VMS that previously displayed a variety of traffic-irrelevant messages. For this, thirty-two participants were divided between a control group and an experimental group (the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…What is more, the lack of a verbal report to confirm an object’s presence does not mean that the object has not been taken into account. Similar to Fisher (1992) and Harms et al (2018), the current study provides further evidence that objects may indeed guide someone’s behavior without this person becoming aware of said objects. It appears that in traffic, one can act without awareness, and regardless of mode of transport.…”
Section: Conclusion and Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…What is more, the lack of a verbal report to confirm an object’s presence does not mean that the object has not been taken into account. Similar to Fisher (1992) and Harms et al (2018), the current study provides further evidence that objects may indeed guide someone’s behavior without this person becoming aware of said objects. It appears that in traffic, one can act without awareness, and regardless of mode of transport.…”
Section: Conclusion and Discussionmentioning
confidence: 51%
“…In other words, most walking is done along routes with which pedestrians are highly familiar. From car driving studies, it is known that increased route familiarity results in increased automaticity and decreased attention for the road (e.g., Martens and Fox, 2007; Charlton and Starkey, 2011, 2013, 2018a; Harms and Brookhuis, 2016; Harms et al, 2018). Largely unknown is whether the same applies for walking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the overall traffic literature, some previous studies on redundancy have shown that when signs are unfamiliar, the inclusion of a redundant text could improve comprehension of the signs and reduce the time for interpretation ( Shinar and Vogelzang, 2013 ). In addition, there are some mixed results regarding the effect of redundancy in Variable Message Signs, in particular, about whether it reduces compliance with the target detour message ( Thomas and Charlton, 2020 ) or not ( Harms et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the speed variation is higher when drivers do not understand the content, whilst the speed profile is stable when drivers comprehend the content. Harms et al [ 12 ] try to understand whether DMS traffic-irrelevant content disturbs the transportation network. Collecting the driving behavior of 32 participants in a driving simulator environment, they observe a significant speed reduction due to reading the DMS content.…”
Section: Introductionmentioning
confidence: 99%